2008
DOI: 10.1186/1471-2407-8-186
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral pulmonary nodules: Relationship between multi-slice spiral CT perfusion imaging and tumor angiogenesis and VEGF expression

Abstract: Background: The aim of this study is to investigate the relationship between16-slice spiral CT perfusion imaging and tumor angiogenesis and VEGF (vascular endothelial growth factor) expression in patients with benign and malignant pulmonary nodules, and differential diagnosis between benign and malignant pulmonary nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 22 publications
3
54
0
Order By: Relevance
“…In fact, several studies have shown that the enhancement of dynamic CT in lung cancer positively correlates with MVD [7][8][9] . In our study, BF of the lesions was positively correlated with MVD.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have shown that the enhancement of dynamic CT in lung cancer positively correlates with MVD [7][8][9] . In our study, BF of the lesions was positively correlated with MVD.…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent baseline CT-p of the primary lung cancer within 1062 (6)(7)(8)(9)(10)(11)(12) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Functional imaging has been claimed to provide more relevant information on tissue viability during treatment monitoring than the standard therapeutic response assessment (RECIST) based on tumour size changes [6][7][8], which is currently used. Among other imaging modalities, CT perfusion (CT-p) recently experienced a progressive increase in interest and acceptance in the radiological community for oncological applications [9][10][11][12][13], including both the diagnostic process and follow-up of lung cancer [14][15][16]. Substantial differences between treatment response to conventional and anti-angiogenic drugs assessed by RECIST criteria and CT-p in patients with lung adenocarcinoma have been evidenced [17].…”
mentioning
confidence: 99%
“…Thus, the analysis of the microcirculation by perfusion CT can be useful in the clinical situation including evaluation of treatment response. Perfusion CT can be used for detection of tumor angiogenesis and in assessing response to antiangiogenic treatment for various cancers [27,28]. Regarding liver imaging, the greatest impact of perfusion CT has been shown in the assessment of patients with HCC, especially that of tumor response to antiangiogenic drugs, such as sorafenib (Nexavar, Bayer Schering Pharma AG, Berlin, Germany) [29,30].…”
Section: Ct Imagingmentioning
confidence: 99%